The power of the sale and purchase deed that must be extended is made by a PPAT whose age exceeds the term of service serving the term of office which is made exceeds the PPAT's term of office based on Law 37 of 1998 - Aslan Noor; Effrem Inocentius Seran; Tetraning Retnowulan S; Ilham Dwi P; Citra Safitra (Jurnal Info Sains : Informatika dan Sains, 2024)
This research aims to analyze the legal force of the Deed of Sale and Purchase made by the temporary Land Deed Making Officer (PPAT), by referring to the provisions contained in Government Regulation Number 37 of 1998. This regulation provides the legal basis for carrying out the duties of the temporary PPAT in making deeds. land certificate. This research uses a normative legal approach. The research results show that the practice of making land deeds by the sub-district head as Temporary Land Deed Making Officer (PPATS) causes several inconsistencies with applicable legal provisions. Research reveals that the signing of deeds is not always carried out in the presence of the sub-district head, but rather in the presence of the village head or village head, and the reading of the deed before signing is never carried out. This discrepancy has the potential to create ambiguity and misunderstanding regarding the contents of the deed between the parties involved. The sub-district head's response to potential lawsuits related to errors in making deeds also reflects a lack of awareness of the legal risks that may arise. Therefore, it is necessary to improve procedures for making land deeds, including increasing understanding of legal risks, to ensure compliance with applicable legal provisions and provide better protection for all parties involved in land transactions.